Koroško mežiško narečje v luči novih glasoslovnih raziskav - Zorko, Zinka (Slavia Centralis, 2009)
This paper presents new phonological studies of the Carinthian Mežica dialect. In Javorje, Črna and in Mežica, long diphthongs changed into monophthongs; Kotlje and Pameče retained the typically Charinthian diphthongal-monophthongal system, Ojstrica retained the Podjuna dialect, and the Mislinja local dialect has the Styrian vowel system typical of southern Pohorje.
Keywords: besedje; dialektologija; glasoslovje; južnopohorski štajerski govori; koroško narečje; mežiško narečje; oblikoslovje; slovenska narečja